SMI Life Goals: Description of a Randomized Trial of a Collaborative Care Model to Improve Outcomes for Persons with Serious Mental Illness - Kilbourne, Amy M. (Contemp Clin Trials, 2014)
BACKGROUND: Persons with serious mental illnesses (SMI) are more likely to die earlier than the general population, primarily due to increased medical burden, particularly from cardiovascular disease (CVD). Life Goals Collaborative Care (LG-CC) is designed to improve health outcomes in SMI through self-management, care management, and provider support. This single-blind randomized controlled effectiveness study will determine whether patients with SMI receiving LG-CC compared to usual care (UC) experience improved physical health in 12 months. METHODS: Patients diagnosed with SMI and at least one CVD risk factor receiving care at a VA mental health clinic were randomized to LG-CC or UC. LG-CC included five self-management sessions covering mental health symptom management reinforced through healthy behavior change; care coordination and health monitoring via a registry, and provider feedback. The primary outcome is change in physical health-related quality of life score (VR-12) from baseline to 12 months. Secondary outcomes include changes in mental health-related quality of life, CVD risk factors (blood pressure, BMI), and physical activity from baseline to 12 months later. RESULTS: Out of 304 enrolled, 139 were randomized to LG-CC and 145 to UC. Among patients completing baseline assessments (N=284); the mean age was 55.2 (SD=10.9; range 28-75 years), 15.6% were women, the majority (62%) were diagnosed with depression, and the majority (63%) were diagnosed with hypertension or were overweight (BMI mean±SD=33.3±6.3). Baseline VR-12 physical health component score was below population norms (50.0±SD=10) at 33.4±11.0. CONCLUSIONS: Findings from this trial may inform initiatives to improve physical health for SMI patient populations.